Apical traction: a novel visual echocardiographic parameter to predict survival in patients with pulmonary hypertension. (1st June 2015) - Unlu, Serkan; Farsalinos, Konstantinos; Ameloot, Koen; Daraban, Ana M.; Ciarka, Agnieszka; Delcroix, Marion; Voigt, Jens-Uwe
Abstract: Aims: In some pulmonary hypertension (PH) patients, we noted a motion pattern where the right ventricular (RV) apex is pulled towards to left ventricle (LV) during systole, caused by traction from the LV ('apical traction', AT). Herein, we characterize patients with AT to investigate its prognostic significance. Methods and results: Echocardiograms of 62 pre-capillary PH patients (42 females, age 61 ± 15 years) were retrospectively analysed. The presence of AT was assessed visually and confirmed by speckle-tracking analysis. Fractional area change (FAC), tricuspid annular plane systolic excursion (TAPSE), RV free-wall longitudinal strain (LS) as well as LV function were measured. A primary end point of death or heart/lung transplantation was set. AT was observed in 31 patients. They had worse functional capacity, lower TAPSE (1.3 ± 0.2 vs. 1.9 ± 0.4, P ≤ 0.001) and FAC (20.3 ± 6.1 vs. 33 ± 7.1%, P ≤ 0.001), worse RV free-wall LS (−12.4 ± 3.4 vs. −20.8 ± 4.9%, P < 0.001), and higher systolic pulmonary arterial pressure (92 ± 15 vs. 75 ± 23, P < 0.001). LV function was similar in both groups. The primary end point occurred in 16 patients with and 8 without AT. AT was an independent predictor of the outcome (HR: 14.826, 95% CI: 1.696−129.642, P = 0.015). Conclusion: AT occurs in RVs with impaired systolic function in PH patients. It may serve as a new, easily to assess visual parameter to predict the outcome in these patients. Its prognostic importance needs to be validated by prospective studies.